Login Tunggal pada Berbagai Social Chat: Studi Kasus Twitter - Wijaya, Marvin Chandra (Zenit, 2013)
At this time a person already has a lot of accounts on cloud computing. Social Chat such as facebook, twitter; email account such  as  Gmail, Microsoft Exchange - EWS, Microsoft Exchange - IMAP, Office 365, Microsoft Exchange - Active sync; storage files such as  Evernote, SkyDrive, Google Drive, Dropbox, Box is already widely used by people. With many accounts, it would appear the confusion when log in (fill in the username and  password), so we need a single sign on for various accounts. By using a single login, user only need to remember one username and one password. Application uses open source program like XAMPP: Apache for web server, PHP for programming adan MYSQL for database.Keywords: cloud computing, single sign on, facebook